Mannan-binding lectin deficiency augments hepatic endoplasmic reticulum stress through IP3R-controlled calcium release. (December 2021) - Chen, Yu; Hu, Mengyao; Deng, Fan; Wang, Ping; Lin, Jingmin; Zheng, Zhuojun; Liu, Yunzhi; Dong, Lijun; Lu, Xiao; Chen, Zhengliang; Zhou, Jia; Zuo, Daming
Highlights: MBL deficiency exacerbates acute liver injury associated with ER stress in mice. Cytosolic calcium overload aggravates ER stress in MBL deficient hepatocytes. MBL deficiency accelerates the IP3R-induced calcium release during hepatic ER stress. MBL deficiency impairs BiP and PERK association, resulting in the activation of the PERK-CHOP pathway. Abstract: The aberrant release of endoplasmic reticulum (ER) calcium leads to the disruption of intracellular calcium homeostasis, which is associated with the occurrence of ER stress and closely related to the pathogenesis of liver damage. Mannan-binding lectin (MBL) is a soluble calcium-dependent protein synthesized primarily in hepatocytes and is a pattern recognition molecule in the innate immune system. MBL deficiency is highly prevalent in the population and has been reported to be associated with susceptibility to several liver diseases. We here showed that genetic MBL ablation strongly sensitized mice to ER stress-induced liver injury. Mechanistic studies established that MBL directly interacted with ER-resident chaperone immunoglobulin heavy chain binding protein (BiP), and MBL deficiency accelerated the separation of PKR-like ER kinase (PERK) from BiP during hepatic ER stress. Moreover, MBL deficiency led to enhanced activation of the PERK-C/EBP-homologous protein (CHOP) pathway and initiates an inositol 1, 4, 5-trisphosphate receptor (IP3R)-mediated calcium release from the ER, thereby aggravating the hepatic ER stress response. Our results demonstrate an unexpected function of MBL in ER calcium homeostasis and ER stress response, thus providing new insight into the liver injury related to ER stress in patients with MBL deficiency. Graphical abstract: Image, graphical abstract